Kepastian Hukum Pelaksanaan Ganti Rugi Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Jannah, Siti Miftahul; Fanciska, Wira; Mau, Hedwig A. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Land is a fundamental human need, both for housing, livelihood, and various development needs. Therefore, land is categorized as a natural resource controlled by the state as regulated in Article 33 paragraph (3) of the 1945 Constitution. The state has the authority to regulate land management for the welfare of the people, including in the context of infrastructure development which often requires land acquisition. However, in practice, the land acquisition process for public interest often causes problems, especially related to the provision of fair compensation for land owners. The imbalance between das sein and das sollen in this study is that there is still legal uncertainty in the implementation of compensation for land acquisition for development in the public interest. Therefore, this study focuses on the analysis of legal certainty in the mechanism for providing compensation for land acquisition in DKI Jakarta Province, with the hope of contributing to the improvement of regulations and land acquisition practices that are fairer and more transparent. The formulation of the problem raised in this study is how to implement compensation for land acquisition for development in the public interest and how to ensure legal certainty in the implementation of compensation for land acquisition for development in the public interest. In this study, the author uses the theory of legal certainty and the theory of authority.The research method used is the normative legal approach. This study uses the statute research approach and the analytical approach which in principle originates from primary legal materials consisting of laws and norms or legal rules, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques.The results of this study show that the implementation of compensation consists of the planning, implementation and results stages. Related to land acquisition for public interest in this case the normalization of the Ciliwung River, sourced from the APBD, namely through the DKI Provincial Government, so that in its implementation it is guided by the Governor's Regulation Number 82 of 2017, in which in the Governor's Regulation compensation is given after the release of rights by the land owner and there is a difference regarding the provision of compensation for land acquisition where based on the Regulation of the Minister of ATR/BPN Number 19 of 2021, compensation is given together with the release of rights, based on the Governor's Regulation Number 82 of 2017, compensation is given after the land owner has first released his land ownership rights, this is one of the obstacles in the implementation of land acquisition for development in the public interest in the Ciliwung River normalization activity. Suggestions are that regional governments in making regional regulations should not conflict with statutory regulations so that there is no confusion in implementing them in the field and it is necessary to harmonize the Regulation of the Minister of ATR/BPN Number 19 of 2021 with the Regulation of the Governor Number 82 of 2017 considering that a regulation that is made must meet the values of certainty, justice and benefit